TRANSFORMATION IN EDUCATION AND CULTURE IN THE POST-COMMUNIST REPUBLIC BULGARIA - Бурдяк, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The paper investigates the development of culture and education in the Republic of Bulgaria and changing the period of democratization. Society rejected the Marxist-Leninist ideology, held deideologization of education and the arts. With the beginning of European integration, Bulgaria started the implementation of a European cultural values, executes programs of the Council of Europe and the EU. Greater financial assistance and support in this matter by various foreign funds and sponsoring organizations. Liberal reforms initiated in Bulgaria in 1989, and especially after 1997 deeply affected the Bulgarian culture. The author believes that the Bulgarians should retain the essential elements and heritage of previous generations, the Enlightenment and humanism, to find a certain synthesis, to develop cultural and educational sector, solving modern problems.